Sociodemographic, clinical profile, and treatment characteristics of oncology patients developing radiation recall phenomenon: Two tertiary care center's experience of an eternal unpredictable phenomenon of cancer treatment - Abhishek Purkayastha; Neelam Sharma; Sachin Taneja; Virender Suhag; Nishant Lohia (Tzu Chi Medical Journal)
Objectives: To determine the socio-demographic and clinical profile of cancer patients developing radiation recall phenomenon or radiation recall dermatitis following chemotherapy administration, previously treated with external irradiation. We assessed its incidence, severity, frequency, differentiation from radio-sensitization and radiation-dermatitis, its correlation with radiation dose and chemotherapeutic agent, and various parameters affecting its occurrence. Materials and Methods: This observational prospective study was designed for 1092/2676 (50.2%) patients of histologically proven carcinoma breast, carcinoma lung, lymphomas, chest wall sarcomas, thymomas, thymic carcinomas, nasopharyngeal cancer, bladder carcinoma, rectal cancer, and metastatic cases who received radiation therapy followed by chemotherapy. Intake, treatment, observation, and follow-up were done from July 2014 to July 2021 for 7 years in two tertiary care cancer institutes of government setup. Results: In our study, majority of recall phenomena were reported in breast carcinoma 43/71 (60.5%) followed by carcinoma esophagus with 07/71 (9.8%) cases. Females developed 54.9% grade-I/II and 90% grade-III/IV recall cases compared to males with 45.1% and 10% cases, respectively (P = 0.005). Median radiation dose used was 45 Gy (dose range 8–70 Gy) (P = 0.656). Docetaxel resulted in 55% recall cases followed by paclitaxel with 12.7% of cases. Combination therapy reported 71.8% of cases compared to monotherapy with 28.2% of cases. Recall-cases recorded in the time period of 3–4 weeks between radiation and chemotherapy were 59/71 (83%) and those reported in >4 weeks were 12/71 (17%). Time-gap between 3 and 4 weeks reported 49% grade-I/II and 100% grade-III/IV recall-cases while time-gap >4 weeks resulted in 26% and 0% cases respectively (P = 0.000). Conclusion: In this study, taxanes and platinum-agents were the most common chemotherapeutic drugs involved in the occurrence of the recall phenomenon. Multi-drug regimens resulted in higher recall cases compared to monotherapy. Radiation dosage did not cause any significant impact. The risk and severity of recall reactions increased with female gender and shorter time-interval between radiation and systemic therapy, while early-onset recall cases displayed greater severity. This precedented but unpredictable phenomenon ceases to be a topic to be discarded in this modern era of highly conformal radiation therapy techniques and targeted cancer therapy.